INSTAGRAM: HOW DO STUDENTS VIEW ON IT IN SPEAKING CLASSROOM - puspita devi; Bianca Virgiana; Merita Auli (Universitas Putera Batam, 2020)
The emergence of the 4.0 era requires the world of education to adapt to technology. Practicing and learning English can take the advantage of the sophisticated technology, especially applications that can be downloaded from students' smart phone. Students acknowledge that English learning done in the classroom is easy for them to forget because it is rarely used in everyday life. Practices done in the classroom do not have enough time for all students to speak English, and students are less motivation to speak English outside the classroom. Integrating Instagram into the process of teaching English speaking is believed could motivate students to speak and increase their speaking ability. Various features on Instagram can help students in doing assignments. Tasks may be packaged attractively within the variety of videos based on a certain theme and uploaded to Instagram. This study aimed to determine students' perceptions related to the use of social media Instagram in learning English speaking. This descriptive study used forty-four students Communication Science in academic year 2019/2020 who took Bahasa Inggris Keahlian. To determine students' perceptions, researchers used questionnaire adopted from Dornyei, 2011. The results of the study showed a positive or good response on students' perceptions towards the use of Instagram in learning English Speaking. Furthermore, Instagram can be used as another medium in teaching speaking. This is strengthened by the increase in self-confidence, learning motivation, and student interest in speaking in English.